Familial esophageal achalasia in mother and son - Raj, Sumesh; Rajan, G. V. (International Journal of Research in Medical Sciences, 2017)
Familial esophageal achalasia a rare presentation, is most often described in monozygotic twins or siblings. Parent/child association is very rare and exhaustive review of the literature found about 5 times as many instances of affected siblings than instances of affected parent/child. Only seven instances of parent/child association have been reported till date. We report a 75 -year-old lady with achalasia cardia and her son who developed the same illness one year later. Mother was treated by Heller's surgery and son is presently on medical management.